2017
DOI: 10.1590/0102-33062016abb0293
|View full text |Cite
|
Sign up to set email alerts
|

Trichomes that secrete substances of a mixed nature in the vegetative and reproductive organs of some species of Moraceae

Abstract: Th is study aimed to obtain new information about the distribution, morphology and content of secretory trichomes present in the vegetative and reproductive organs of four species of Moraceae: Artocarpus heterophyllus, Dorstenia cayapia, Maclura tinctoria and Sorocea bonplandii. Stem, leaf, fl ower and infl orescence samples were processed for scanning electron and light microscopy. Th e species have secretory trichomes on the leaf blade, petiole and stem and also on the infl orescence and fl owers of D. cayap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
3
7
0
1
Order By: Relevance
“…Glandular hairs with a globular 1-2 cellular head, and unicellular stalk and papillary hairs. Most of these hairs had been reported previously for members of Moraceae family, 15,16 but they were better described by Jacomassi et al 14 Elevated above epidermis hairs seen in this study were not previously reported for this genus. Also, there is no previous report of pluricellular rosette-like bases of hairs, probably because most of the studies do not include diaphanized leaf, but were previously described for other Moraceae species.…”
Section: Discussionsupporting
confidence: 67%
“…Glandular hairs with a globular 1-2 cellular head, and unicellular stalk and papillary hairs. Most of these hairs had been reported previously for members of Moraceae family, 15,16 but they were better described by Jacomassi et al 14 Elevated above epidermis hairs seen in this study were not previously reported for this genus. Also, there is no previous report of pluricellular rosette-like bases of hairs, probably because most of the studies do not include diaphanized leaf, but were previously described for other Moraceae species.…”
Section: Discussionsupporting
confidence: 67%
“…Other substances seem to be enrolled in adhesion of pollen, as reported by Schnetzler et al (2017) for polysaccharides in trichomes of Dorstenia cayapia (Moraceae). In oil-producing Cucurbitaceae, Possobom & Machado (2017) reported the adhesive properties of oil from male flowers, which adhere the pollen grain to the body of floral visitors.…”
Section: Discussionmentioning
confidence: 67%
“…This is even the case for very small plant organs, where there may be pressure from spider mites or other herbivores (Walters 2017). Many secretions also have dual roles (Schnetzler et al 2017) as both antiherbivore and antimicrobial (Farmer 2014). The tip of the gland could act as a physical defense but when broken, for instance, by an arthropod, could release its toxins (Walters 2017).…”
Section: Plant-animal Relationshipsmentioning
confidence: 99%